DP4-AI automated NMR data analysis: straight from spectrometer to structure. Issue 17 (10th March 2020) - Howarth, Alexander; Ermanis, Kristaps; Goodman, Jonathan M.
Abstract : A robust system for automatic processing and assignment of raw 13 C and 1 H NMR data DP4-AI has been developed and integrated into our computational organic molecule structure elucidation workflow. Abstract : A robust system for automatic processing and assignment of raw 13 C and 1 H NMR data DP4-AI has been developed and integrated into our computational organic molecule structure elucidation workflow. Starting from a molecular structure with undefined stereochemistry or other structural uncertainty, this system allows for completely automated structure elucidation. Methods for NMR peak picking using objective model selection and algorithms for matching the calculated 13 C and 1 H NMR shifts to peaks in noisy experimental NMR data were developed. DP4-AI achieved a 60-fold increase in processing speed, and near-elimination of the need for scientist time, when rigorously evaluated using a challenging test set of molecules. DP4-AI represents a leap forward in NMR structure elucidation and a step-change in the functionality of DP4. It enables high-throughput analyses of databases and large sets of molecules, which were previously impossible, and paves the way for the discovery of new structural information through machine learning. This new functionality has been coupled with an intuitive GUI and is available as open-source software at ; https://github.com/KristapsE/DP4-AI .